Strategies to reduce the flammability of organic phase change Materials: A review. (1st January 2022) - Png, Zhuang Mao; Soo, Xiang Yun Debbie; Chua, Ming Hui; Ong, Pin Jin; Suwardi, Ady; Tan, Chee Kiang Ivan; Xu, Jianwei; Zhu, Qiang
Graphical abstract: Abstract: Organic Phase Change Materials (oPCMs) are practical and efficient materials in regulating temperature changes, with broad applications including building material, textiles, and food packaging. However, their flammability poses the main challenge to their widespread applications. This review summarizes various approaches to reduce the flammability of oPCMs including incorporation of flame retardants in shape stabilized PCMs and microencapsulated PCMs, chemical transformations and surface coating, paying particular attentions to the flammability parameters such as limiting oxygen index (LOI), total heat released (THR), peak heat release rate (pHRR) as well as the mechanisms of fire retardancy. Flame-retardant oPCM for practical applications such as plasterboards and fabrics will be highlighted. Further strategies to enhance flame retardant properties of oPCM, such as, incorporation of synergistic flame retardants, chemical modification of PCM (e.g. intrinsically flame-retardant oPCM), have been proposed and commented in the conclusion of this paper.